Computed Tomography Registration-Derived Regional Ventilation Indices Compared to Global Lung Function Parameters in Patients With COPD - Cohen, Julien; Shekarnabi, Mehdi; Destors, Marie; Tamisier, Renaud; Bouzon, Sandrine; Orkisz, Maciej; Ferretti, Gilbert R.; Pépin, Jean-Louis; Bayat, Sam (Frontiers in Physiology, 2022)
CT registration indices provide data on regional lung functional changes in COPD. However, because unlike spirometry which involves dynamic maximal breathing manoeuvres CT-based functional parameters are assessed between two static breath-holds, it is not clear how regional and global lung function parameters relate to each other. We assessed the relationship between CT-density change (dHU), specific volume change (dsV) and regional lung tissue deformation (J) with global spirometric and plethysmographic parameters, gas exchange, exercise capacity, dyspnoea, and disease stage in a prospective cohort study in 102 COPD patients. There were positive correlations between dHU, dsV and J with spirometric variables, DLCO and gas exchange, 6-minute walking distance and negative correlations with plethysmographic lung volumes and indices of trapping and lung distension as well as GOLD stage. Stepwise regression identified FEV1/FVC (standardised =0.429, p<0.0001), RV/TLV (=-0.37, p<0.0001) and BMI (=0.27, p=<0.001) as the strongest predictors of CT intensity-based metrics dHU, with similar findings for dsV, while FEV1/FVC (=0.32, p=<0.001) and RV/TLV (=-0.48, p=<0.0001) were identified as those for J. These data suggest that regional lung function is determined by two major pathophysiological processes involved in global lung function deterioration in COPD: chronic airflow obstruction and gas trapping, with an additional contribution of nutritional status, which in turn determines respiratory muscle strength. Our data confirm previous findings in the literature suggesting the potential of CT image-based regional lung function metrics as biomarkers of disease progression, and provide a mechanistic insight into the interpretation of regional lung function indices in patients with COPD.